(untitled) (Archives of Clinical and Medical Case Reports, 2018)
Ovarian tumors in children are uncommon, whether benign or malignant. The diagnosis must be considered, however, when there is unexplained pelvic pain. A palpable mass further raises suspicion and warrants prompt pelvic ultrasound. On occasion, precocious puberty and hirsutism will assist in the clinical evaluation. Surgery is the primary treatment for all ovarian tumors. Attempt at ovarian salvage to preserve fertility is essential. A case report follows, describing a large benign right ovarian tumor whose diagnosis was delayed because of unrelated clinical problems.